2013
DOI: 10.1155/2013/140508
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Pleuropulmonary Blastoma in a Child with Jejunal Hamartomas

Abstract: We report a rare case of 9-month-old girl who presented with a choking episode and was found to have an incidental finding of a lung cyst and iron deficiency anemia leading to the diagnosis of pleuropulmonary blastoma (PPB) and a jejunal hamartoma. Our patient is the eighth that has been reported with the association of PPB with jejunal hamartoma and the first one in the radiological literature. PPB is the pulmonary analog of other dysontogenetic neoplasms in childhood. A biological sequence has been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…(a completely cystic neoplasm, i.e., more benign than PPB type II) has been raised in the literature as a concern in the radiologic differential diagnosis of CPAM, but to our knowledge, our study is the first to raise PPB type II in the differential diagnosis of this entity. 3,4,16 The results of our study, which showed nonenhancing solid component of BA in con- demonstrating a relatively high frequency of coexistence when dissecting microscopy is used instead of naked-eye examination. 13 Future studies focusing on direct radiology and pathology correlation of various congenital lung lesions will be helpful for confirmation of the postulated "bronchial atresia sequence" theory for the development of various different types of congenital lung malformations.…”
Section: Additional Uncategorized Abnormalities On Thoracic Mdct Studymentioning
confidence: 53%
See 1 more Smart Citation
“…(a completely cystic neoplasm, i.e., more benign than PPB type II) has been raised in the literature as a concern in the radiologic differential diagnosis of CPAM, but to our knowledge, our study is the first to raise PPB type II in the differential diagnosis of this entity. 3,4,16 The results of our study, which showed nonenhancing solid component of BA in con- demonstrating a relatively high frequency of coexistence when dissecting microscopy is used instead of naked-eye examination. 13 Future studies focusing on direct radiology and pathology correlation of various congenital lung lesions will be helpful for confirmation of the postulated "bronchial atresia sequence" theory for the development of various different types of congenital lung malformations.…”
Section: Additional Uncategorized Abnormalities On Thoracic Mdct Studymentioning
confidence: 53%
“…In fact, type II pleuropulmonary blastoma and the combined BA-CPAM congenital lung lesion may be difficult to differentiate based on imaging findings alone due to the similarity of their radiologic appearance. In the past, PPB type I (a completely cystic neoplasm, i.e., more benign than PPB type II) has been raised in the literature as a concern in the radiologic differential diagnosis of CPAM, but to our knowledge, our study is the first to raise PPB type II in the differential diagnosis of this entity 3,4,16. The results of our study, which showed nonenhancing solid component of BA in contrast to the enhancing solid component in type II pleuropulmonary blastoma, should allow for confident differentiation of PPB type II from this combined BA-CPAM congenital lung lesion, on contrast-enhanced thoracic MDCT from now on.…”
mentioning
confidence: 78%
“…Other better documented cases of hamartomatous polyps in DICER1 carriers include a 19-year-old female with a type I PPB, bilateral pCNs and an ileal intussusception due to a 3.2 cm “juvenile polyp” 90 . Other examples of intestinal polyps include a 2-year-old girl with an “hamartomatous esophageal polyp” 68 and a 9-month-old girl with a type I PPB and a jejunal hamartomatous polyp 115 . Five children with PPB, pCN and small intestinal intussusception due to polyps and two children with PPB and small intestinal polyp have also been reported 116 .…”
Section: The Gastrointestinal Systemmentioning
confidence: 99%
“…Pleuropulmonary Blastoma (PPB), Type 1 Primary neoplasms of the lung are rare, but the most common of these is the childhood form of PPB, a blastemal tumor similar to Wilm's tumor [23,24]. Mutations in the DICER gene have been described with PPB [25]. PPB has three different main subtypes: cystic [type 1], combined cystic and solid [type 2], and solid [type 3] [26].…”
Section: Traumatic Lung Lesionmentioning
confidence: 99%
“…If it recurs after treatment, it tends to recur as a more aggressive subtype. Children with PPB are at increased risk of other childhood tumors [24][25][26]. Tumors associated with PPB include cystic nephroma, Sertoli-Leydig tumors of the ovaries, and small bowel polyps in the pediatric population [23][24][25][26].…”
Section: Traumatic Lung Lesionmentioning
confidence: 99%